PEMBERDAYAAN MASYARAKAT DI DESA TUMPATAN NIBUNG UNTUK PEMBUATAN KOMPOS DALAM RANGKA MENGHASILKAN SAYUR ORGANIK - Dedi Kusbiantoro; Nurhayati Nurhayati; Jalilah Ilmiha (Jurnal Pengabdian Mitra Masyarakat, 2023)
Tumpatan Nibung Village is located in Batang Kuis District, Deli Serdang Regency, North Sumatra Province. The people of Tumpatan Nibung Village live from agriculture, which consists of 90 percent of their living from cultivating paddy rice and 10 percent cultivating vegetable crops. The land in this village is rainfed land which has limited water, because it does not have irrigation so that the need for water depends on rainfall. The purpose of this service is to increase farmers' understanding of the benefits of using organic fertilizers both for the environment and to reduce the cost of buying chemical fertilizers and to provide added value for organic products that can increase income and also aims to transfer technology by providing training to farmers on how to make organic fertilizers derived from available in the village. The first method used was counseling to Farmer Groups with the theme of the benefits of organic fertilizers for the environment, calculating the cost of using organic fertilizers and the added value of organic fertilizers which can increase farmers' income. The second method used is training in making organic fertilizers. The third method is a demonstration plot for making organic fertilizer and cultivating vegetable crops using organic fertilizer.